A Bacteria‐Based Remotely Tunable Photonic Device. Issue 1 (18th November 2016) - Bennet, Mathieu; Gur, Dvir; Yoon, Jonghee; Park, YongKeun; Faivre, Damien
Abstract : The bacteria‐based photonic device is analogous to liquid‐crystal‐based devices where the liquid crystals and an electric field are replaced by magnetic bacteria and a magnetic field, respectively. The controlled orientation of the bacteria in the device is used to tune the intensity and the polarization of the light.